Emitexts and Paratexts: Propaganda in EVE Online. (July 2015) - Carter, Marcus
In EVE Online, powerful alliances of thousands of players wage long war campaigns over in-game sovereignty, wealth, power, and status. The larger of these wars involve—two to three battles a day across multiple time zones demanding thousands of players and considerable in-game wealth. As with real wars, the morale of combatants plays a crucial role in the success of a campaign. In this article, I discuss the propaganda produced as a component of these wars and the crucial role that it plays in EVE 's virtual warfare. Leveraging broader Internet memes; "nerd" tropes; in-jokes; game history; and racial, cultural, and sexist stereotypes, these evocative images serve to bolster support and demoralize opponents. I argue that propaganda can be conceptualized as a form of paratext that emerges from within the game as part of play, rather than a peripheral industry that surrounds it. Consequently, I propose the term "emitext" to define this persuasive media.